IMPLEMENTASI WAKAF TUNAI DALAM UU NO 41 TAHUN 2004 DI BANK MUAMALAT INDONESIA LAMPUNG TIMUR - Fatimah, Siti (AS-SALAM, 2015)
Waqf is one instrument in Islamic economy that aims to achievethe objectives of Islamic economics is to realize a prosperous life.Endowments are still seen as practice for the rich, because thepayment is identical to the endowments of land and buildings. CashWaqf has accommodated formal judicial since the enactment of LawNo. 41 of 2004. While the technical rules of cash endowments, newlypublished in 2009 Bank Muamalat Indonesia readiness so as LKSPWU and the Ministry of Religious Affairs in the implementation ofcash waqf lampungtimur interesting to study. Related to the bankâsreadiness Muamalat lampung east, the principle has been preparedby the circular of Bank Muamalat operations center. Howeverunfortunate lampung east bank Muamalat not socialize and publicizethat they are as LKS-PWU. While the readiness of the Ministry ofReligious lampungTimur very helpful terlaksanyanya cash waqf,where they have not received and know the Minister of ReligiousAffairs Regulation No. 4 of 2009 on Administration of Registrationof Cash Waqf. Therefore socialization cash endowments in order itsimplementation is very important.Keywords: Cash Waqf, Implementation.